Tail risk hedging: The search for cheap options - NEO, Poh Ling (Institutional Knowledge at Singapore Management University, 2023)
The authors find that a simple heuristic of sorting liquid equity options by dollar price to construct a portfolio of cheap put options leads to a surprisingly robust hedge for tail risk – the superior performance holds even when compared against more advanced empirical strategies. Further investigation reveals the asymmetry in market correlation under different market conditions as the mechanism of this robust hedging performance. The cheap options selected by the heuristic comprises of stocks with diverse firm characteristics. The correlation spike accompanying tail risk events leads to the majority of these put options moving into-the-money (ITM), thus compensating the losses incurred on a benchmark S&P 500 index holding. On the other hand, during normal market conditions, the lower market correlation leads to some of these put options expiring ITM, mitigating the portfolio drag effect through diversification.